Exploring the Effectiveness of Mobile Smartphones in Teaching Islamic Studies among Senior Secondary Schools - Jibril, Ayuba Olaniyi; Kayode, Abdulkareem Musa (Universitas Pendidikan Ganesha, 2023)
The need for Islamic Religious teachers in Senior High Schools to fully integrate ICT tools, especially smartphones, in enhancing effective and efficient teaching in digital processes compared to traditional teaching methods should not be underestimated. This study aims to analyze the integration of ICT mobile smartphones for effective teaching of Islamic studies among senior secondary schools. This study adopted research quantitative method of research. The instrument used for data collection was validated by three experts in Test & Measurement who found it appropriate for this study. A simple random sampling technique was used to select 194 out of 307 senior secondary school teachers of Islamic studies as the sample size of the study. A questionnaire titled